It doesn't have to be crazy at work - Fried, Jason; Hansson, David Heinemeier (Harper Business, an imprint of HarperCollinsPublishers, 2018)
Presents a timely manifesto that rejects popular values about high stress and burnout as tenets of success, outlining an alternative path to building a calm, focused organization that eliminates waste.